Association between sarcopenia and prognosis of hepatocellular carcinoma: A systematic review and meta-analysis - Jiang, Chuan; Wang, Yanyan; Fu, Wei; Zhang, Guozhuan; Feng, Xiaoshan; Wang, Xing; Wang, Fang; Zhang, Le; Deng, Yang (Frontiers in Nutrition, 2022)
Background: Sarcopenia, characterized by the loss of muscle mass, strength, and physical ability, occurs with aging and certain chronic illnesses such as chronic liver diseases and cancer. Sarcopenia is common in liver cirrhosis and hepatocellular carcinoma (HCC). Previous reports of association between sarcopenia and prognosis of HCC have been inconsistent. Therefore, the present systematic review and meta-analysis aimed to investigate the impact of sarcopenia on the survival of patients with HCC. Methods: A systematic literature search was conducted using PubMed, EMBASE, and Web of Science electronic databases from inception to May 1st, 2022. We included retrospective or prospective studies investigating the association between sarcopenia and overall survival (OS) and/or progression free survival (PFS) of HCC. We applied the Quality in Prognosis Studies (QUIPS) instrument to evaluate the risk of bias and quality of included studies. The primary and secondary outcomes were the associations of sarcopenia with OS and PFS, respectively, expressed by a pooled hazard ratio (HR) and corresponding 95% confidence interval (CI). Subgroup analysis and sensitivity analysis were performed. We further evaluated the publication bias by the funnel plot and Begg’s test. Results: A total of 42 studies comprising 8,445 patients were included. The majority of included studies were at an overall low risk of bias. The pooled prevalence of sarcopenia was 39% (95% CI: 33%-45%) (n = 8203). Sarcopenia was associated with an increased risk of shorter OS, with a pooled adjusted HR of 1.84 (95% CI: 1.62-2.09). An independent association between sarcopenia and reduced PFS was observed (HR = 1.33, 95% CI: 1.12-1.56). Conclusions: The prevalence of sarcopenia was approximately 39% among patients with HCC. Sarcopenia was independently associated with reduced OS and PFS in HCC irrespective of treatment modalities. It is imperative that interventions aimed at alleviating sarcopenia and restoring muscle mass be implemented in order to improve the survival of patients with HCC.